ANALISIS KELAYAKAN DAN PRODUKSI USAHA PEMBENIHAN LELE DI KABUPATEN SLEMAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
The purpose of this study was to determine the seeding farm income and analyzing factors affecting seed production of catfish. The method used in this research is quantitative descriptive. The data analyzed were the primary data and secondary data. Selection of study sites intentionally (purposive) that Sleman because Sleman is the center of catfish farming. Sleman be regarded as a center for Sleman conduct all activities ranging from upstream to downstream activities of catfish farming. The study was conducted in 4 Districts are located in the District Seyegan Sleman District, District Moyudan, Kalasan and District Godean. The sampling techniques was using four that area sampling, purposive sampling, proportional random sampling and snowball sampling. Data were analyzed by using: analysis of revenue, and margin analysis: Cobb-Douglas production function. The analysis showed that income catfish fry farmers during the first period (2 months) with an area of 133, 68 m2 is Rp. 9,241,647, -. Value of R/C ratio catfish fry farmers for 1 period was 3.79. Increasing the number of worms and an amount has significant positive effect on fry production of catfish.